Efektivitas Penggunaan Media Instagram Komik dalam Pembelajaran Menulis Sinopsis Teks Cerita Bima Bungkus pada Siswa Kelas X Di SMA Negeri 9 semarang Tahun ajaran 2022-2023 - laila, heni nur; Zaidah, Nuning; Sunarya, Sunarya (JISABDA: Jurnal Ilmiah Sastra dan Bahasa Daerah, Serta Pengajarannya, 2023)
This study aims to describe in detail the effectiveness of using Instagram Comic media in learning to write a synopsis of the Bima Bungkus story text for class X students at SMA Negeri 9 Semarang in the 2022-2023 Academic Year. This is motivated by students' lack of interest in reading and students' lack of interest in wayang stories. Inadequate use will affect student learning outcomes. So we need media that is adequate and can attract students' learning interest in the process of understanding the story of wayang Bima Bungkus. Thus, the formulation of the problem obtained is how effective is the use of Instagram Comic media in learning to write a synopsis of the story text Bima Bungkus in class X students.This research is included in the experimental research, with the type of research One-Group Pretests-Posttest Design. The data obtained will be used to determine the effect of treatment on controlled conditions. The approach used is descriptive qualitative. The data obtained from this study were in the form of test results, questionnaires and interviews.After analyzing the data, the following research results were obtained: From the results of the learning competency test scores using Instagram Comic media, the final average score of the competency test was 93.58. While learning that only uses Power Point media, gets an average final competency test score of 34.70. From the acquisition of the final average score of the competency test, it can be said that the final average score of the first meeting competency test using only Power Point media is lower than the predetermined KKM score of 75 and the final average score of the second meeting competency test those using Instagram Comic media are higher than the specified KKM score. Thus, the use of Instagram Comic media in learning to write a synopsis of the Bima Bungkus story text for class X students can have an influence on the achievement of the specified learning objectives.